KEEFEKTIFAN PENGGUNAAN METODE INQUIRY DALAM MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 3 BONE - Muhammad Asdar; A. Nurhabibi Marwil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effectiveness of the use of the Inquiry method in teaching expository text writing to grade X students of SMA Negeri 3 Bone. The background of this study is based on students' low ability to develop data-based arguments, organize paragraphs logically, and the lack of ability to analyze issues before writing. The Inquiry method was chosen because it places students as information discoverers through the process of asking questions, investigating, collecting data, analyzing facts, and drawing conclusions before being written in expository writing. The results of the description show that the Inquiry method is effective in improving the ability to write expository texts, especially in the aspects of argument quality, accuracy of supporting data, and paragraph coherence. These findings confirm that the use of the Inquiry method can be a relevant and innovative pedagogical alternative for Indonesian language teachers at the high school level, especially in developing evidence-based writing skills.